Frekuensi Penyiraman Larutan Urin Domba terhadap Tinggi Tanaman, Jumlah Daun dan Produksi Segar Hidroponik Fodder Jagung (Zea mays) - Tri Ida Wahyu Kustyorini; Aju Tjatur Nugroho Krisnaningsih; Didakus Santitores (Fakultas Peternakan, Universitas PGRI Kanjuruhan Malang, 2020)
The purpose of this study was to determine the effect of watering frequency of sheep urine solution on plant height, number of leaves and plant production on corn fodder (Zea mays). The material used in this study was 3.750 corn, sheep urine and water. The method used in this study was a field experiment using a Completely Randomized Design (CRD) consisting of 3 treatments and 5 replications. The research treatment consisted of P1 (watering 1 time /day), P2 (watering 2 times /day) and P3 (watering 3 times /day) with 10% sheep urine solution. The variables observed in this study were plant height, number of leaves and plant production. The analysis used was analysis of variance if there was an effect then continued with the LSD test. Based on the results of the study showed that the frequency of watering the urine solution of sheep gave no significant effect (P> 0.05) on plant height, number of leaves and gave a very significant effect (P <0.01) on plant production. The highest plant height in P2 (36.76 cm), the highest number of leaves in P2 (3.40 strands) and the highest plant production in P2 (374.80 grams). The conclusion of this study is the watering of sheep urine solution 2 times a day giving the best results on plant height, leaf number and fresh hydroponic production of corn fodder (Zea mays).